Lagrange's equations for holonomic systems with rigid bodies (Archives of Mechanics - Test, 1997)
A holonomic system is considered which consists of rigid bodies and material points. Any rigid body is regarded as a continuous system and its position is described by the so-called angular vectors. Starting from the characterization of the constraints and using some identities for the angular vectors, the motion of the holonomic system is shown to be governed by the usual Lagrange's equations. The essential role of the angular vectors is emphasized through comparison with a previous approach.